Myocardial infarction: a critical role of macrophages in cardiac remodeling - Weinberger, Tobias; Schulz, Christian (Frontiers in Physiology, 2015)
Ischemic heart disease is a common condition and a leading cause of mortality and morbidity. Macrophages, besides their role in host defense and tissue homeostasis, are critical players in the pathophysiological processes induced by myocardial infarction. In this article we will summarize the current understanding of the role of monocytes and macrophages in myocardial damage and cardiac remodeling in relation to their origin and developmental paths. Furthermore, we describe their potential implications in therapeutic strategies to modulate myocardial healing and regeneration.